PENGEMBANGAN SARANA WISATA DALAM RANGKA MENUNJANG DESA WISATA DI DESA LANTAN, KECAMATAN BATUKLIANG UTARA, KABUPATEN LOMBOK TENGAH - Imran; Nasip, Harun; Aryandi, Rifani Dwi; Muttaqim, Muhammad Imam; Uyun, Ratih Kuratul; Aulia, Nabila; Marmara, Agisha Talitha; Annisa, Karima Nur; Febrianti, Lisa; Wulandari, Denek Bini Pradila; Sayuti, Rosiady Husaenie (Jurnal Wicara, 2024)
Real Work Lectures are a comprehensive application in the field of scientific disciplines of the theories they have into a real form of community service. This year, Mataram University is holding a Real Work Lecture program based on the Village Community Empowerment (PMD) method which is aimed at developing a spirit of empathy and concern for problems that occur in society, making the nation's life intelligent, and realizing community welfare. Lantan Village is a village that has potential, one of which is in the tourism sector. However, development activities and utilization of this potential have not been carried out optimally by the community. Therefore, KKN PMD aims to overcome existing problems in villages, especially in utilizing village potential in the tourism sector. The method used in implementing this activity is the participatory method and focus group discussion (FGD) which is applied in (1) structuring tourist locations, (2) organizing village administration, (3) teaching activities and providing literacy corners and (4) lighting installation activities. travel and socialization. The result of this activity is that the camping ground tourist location in Sumberan hamlet is quite well organized. Apart from that, through village administration activities we can provide good services to the community, help improve students' reading and numeracy skills, provide lighting facilities for the Gubuk Makam hamlet community so they feel safe and form community awareness regarding the management of existing village potential. The results of these activities show that these activities can help overcome problems in society related to the development of existing potential.